2018
DOI: 10.3390/molecules23020372
|View full text |Cite
|
Sign up to set email alerts
|

Nectandra grandiflora By-Products Obtained by Alternative Extraction Methods as a Source of Phytochemicals with Antioxidant and Antifungal Properties

Abstract: Nectandra grandiflora Nees (Lauraceae) is a Brazilian native tree recognized by its durable wood and the antioxidant compounds of its leaves. Taking into account that the forest industry offers the opportunity to recover active compounds from its residues and by-products, this study identifies and underlines the potential of natural products from Nectandra grandiflora that can add value to the forest exploitation. This study shows the effect of three different extraction methods: conventional (CE), ultrasound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Cg is the average concentration in the control samples and Tg is the average concentration in the treated sample [22,23].…”
Section: Growth Intensity (Gi) Evaluationmentioning
confidence: 99%
“…Cg is the average concentration in the control samples and Tg is the average concentration in the treated sample [22,23].…”
Section: Growth Intensity (Gi) Evaluationmentioning
confidence: 99%
“…Ferreira et al (2018) found high activity for Nectandra cuspidata leaves with a IC50 of 6.54 ± 0.10 µg.mL -1 . In studies on Nectandra grandiflora, Silva et al (2018) observed inhibition of about 80% of the DPPH • radical. González; Mosquera (2019) recorded a IC50 of 50.63 µg.mL -1 for the Nectandra acutifolia extract by the DPPH assay, however, a higher value than that found for N. megapotamica in this study.…”
Section: Resultsmentioning
confidence: 98%
“…amazonum [ 41 ], N . cissiflora [ 42 ], vitexin, isovitexin, and epicatechin in Nectandra cuspidata [ 43 ] and quercetin-3- O -rhamnoside in Nectandra grandiflora [ 44 ]. Thus, the other compounds of the Nectandra genus identified herein (peak 1, 3, 4, 5, 6, 7, 9, 10, 11, 13, 14, 15, 16, 18, 21, 22 and 23 ) are described for the first time, demonstrating the capacity of N .…”
Section: Resultsmentioning
confidence: 99%